Pembekalan Pengetahuan Pemanfaatan Jenis Sampah dan Klasifikasinya pada Anak Usia Sekolah Sejak Dini Sebagai Suatu Sumber Energi Terbarukan - Bambang Panji Asmara; Ikhsan Hidayat; Zainudin Bonok; Wahab Musa (Electrical Engineering Department Faculty of Engineering State University of Gorontalo, 2023)
Carry out community service activities for teaching staff in an effort to carry out one of the tasks as the implementation of one of the tridarma of higher education) - one of which is this service is an effort by Gorontalo State University to implement the Tridarma of Higher Education to contribute science and technology to society Based on this, we propose a Community Service activity at SDIT School in Kota Tengah District, Gorontalo City with the aim of this service is to provide knowledge to school-age children from an early age so they can have an understanding of waste utilization and how to classify it so that they can apply it in their daily environment. so that a clean environment is created and the waste can be used as a source of renewable energy. The expected outputs from this activity are 1) to equip students with knowledge about waste and its benefits, 2) that waste is managed according to the disposal site and its classification, so that it is easy to use as an energy source in their urban areas so that it accelerates its implementation and can be maintained a meaningful and beneficial environment